PERSEBARAN DAN KARAKTERISASI MORFOLOGI LENGKIR (Tacca leontopetaloides L. Kuntze) SEBAGAI SUMBER PANGAN DI PULAU BANGKA - Lanita Sakila; Henri Henri; Sajidin Sajidin (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2020)
Food plants is a type of plant in which there are carbohydrates and proteins that can be used as a source of energy for humans. one of which is lengkir. Lengkir growth wild and can found started from the edge of the sea 0 mdpl to a height of about 220 mdpl. This study aims to inventory and characterize lengkir in Bangka island. The research method consists of determining the location of the distributioan lengkir by purposive sampling and morphological characterization. The results showed that the number of individuals most found in Bangka Tengah is 678 individuals and the least in the city of Pangkalpinang is 16 individuals. The conclusion of this study that the lengkir found in all districts of the island of Bangka with the pattern of distribution groups. A map of the distribution of lengkir on the Bangka island is expected to contribute to the availability of the location information and the conditions of existence lengkir in Bangka island.